Computational Efficiency Trade-offs in Scaling Kimi k1.5 RL Training vs R1-7B Pretraining - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 4 peer-reviewed papers addressing the following research question: What is the computational efficiency trade-off when scaling Kimi k1.5's RL-based training compared to R1-7B's pretraining, measured by throughput on the GEMM or PopQA benchmarks. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 2.2/10. This report is a machine-generated
Machine-generated literature synthesis.